Personal Information Management Systems - Heleen Janssen; Jatinder Singh (Internet Policy Review, 2022)
Personal Information Management Systems (PIMS) seek to empower users by equipping them with mechanisms for mediating, monitoring and controlling how their data is accessed, used, or shared.
Keywords: 300; PIMS; Personal data stores; Data processing; Decentralisation; Userempowerment; Self-regulation